Billionaire at the barricades : the populist revolution from Reagan to Trump - Ingraham, Laura (New York, NY : All Points Books, 2017)
"Americans didn't just go to the polls in 2016. They joined a movement that swept the unlikeliest of candidates, Donald J. Trump, into the Oval Office. But can he complete his agenda? Or will his opponents in the media, the protestor class, and the bipartisan political establishment block his efforts and choke off the movement he represents? In Billionaire at the Barricades, bestselling author Laura Ingraham--the most-listened-to woman in political talk radio--gives readers a front-row seat to the seminal moments of the populist revolution as she witnessed it. In a work at once personal and prescient, Ingraham reveals the origins of this misunderstood movement and its connection to the Trump presidency. She unmasks the opposition, forecasts the future of the "Make America Great Again" agenda, and offers her own prescriptions for bringing real change to the swamp of Washington. Unlike so many of her media colleagues, Ingraham instantly grasped Trump's appeal and defied those who repeatedly wrote his political obituary. Now she confronts the president's critics and responds to those who deny the bipartisan appeal of his populist, pro-life, pro-growth, American First agenda. The Trump agenda cannot be considered in isolation but is the fulfillment of a movement's yearnings, Ingraham writes. With sharp humor and insight she traces the DNA of the populist movement from Barry Goldwater's quixotic 1964 campaign, to Richard Nixon's Silent Majority, to Ronald Reagan's smashing electoral victories. Populism fueled the insurgency campaigns of Buchanan and Perot, the election of George W. Bush, and the Tea Party rallies during the Obama presidency. But it was a political novice, a Manhattan billionaire, who would prove the movement's most vocal champion. This is the inside story of his victory and the fitful struggle to enact his agenda. Ingraham reveals previously unreported details behind Trump's victory and outlines the pitfalls ahead, mapping out where she thinks the populist revolution should (and will) take this country--whether fully realized by this administration or not. No politically engaged American can afford to ignore Ingraham's definitive take on the past, present, and future of the populist movement."--Inside jacket flaps.
Introduction: an early warning sign -- Rebel with a cause: Ronald Reagan and the populist wave -- King George's new world order: the GOP establishment strikes back -- Clinton's perverse populism: from Bubba to Barbra Streisand -- Endless war & shamnesty: "W" is for waste -- The great GOP unifier: Barack Obama unites conservatives, inspires the Tea Party -- The rise of Trump: the Republican presidential primary -- The people's victory: Donald Trump's unconventional convention -- Populism's last stand: the movement's revolutionary win -- Where does it go from here?: President Trump & the populist movement.
Includes bibliographical references and index.
NonFiction
Keywords: Trump, Donald, -- 1946- -- Influence; Trump, Donald, -- 1946-; Trump, Donald -- 1946-; United States -- Politics and government -- 1989-; Right and left (Political science) -- United States; Presidents -- United States -- Election -- 2016.; Populism -- United States -- History; POLITICAL SCIENCE -- American Government -- General; POLITICAL SCIENCE -- Commentary & Opinion; POLITICAL SCIENCE -- Comparative Politics; POLITICAL SCIENCE -- Political Ideologies -- General; POLITICAL SCIENCE -- Public Policy -- Social Policy; Influence (Literary, artistic, etc.); Politics and Government; Populism; Presidents -- Election; Right and left (Political science); United States; Populism -- United States; Presidents -- United States -- Election -- 2016.; Since 1989; History